ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV DI SEKOLAH DASAR NEGERI SONOSEWU - astuti, linda dwi; Septina , Allya Zulfa; Rivandy , Ray; Danuri , Danuri (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
Mathematics has an important role in various disciplines in developing human thinking, by studying mathematics, students are more critical in understanding problems in daily life. This research aims to analyze the factors that cause mathematics learning difficulties experienced by class IV students at SDN Sonosewu. This research method uses a qualitative approach with a case study design. The subjects of this research were class teachers and class IV students who were identified as having difficulties learning mathematics. Data collection techniques in this research are observation, interviews, documentation and field notes. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions/verification. The results of the research show that 1) The difficulties in learning mathematics experienced by class IV students at SDN Sonosewu are difficulty understanding the concept of fractions, difficulty in calculating multiplication and division skills, and difficulty solving questions in the form of story problems. 2) Factors that cause difficulties in learning mathematics consist of internal factors and external factors. Internal factors that cause learning difficulties are sensory abilities, students' interest in mathematics lessons is still low, learning attitudes are still low, students' motivation and habits in learning mathematics are also low. Meanwhile, external factors that cause learning difficulties are the teacher's less attractive teaching methods, the teacher's relationship with students, and the lack of learning facilities.